A simplified approach for estimating the ventilatory and respiratory compensation thresholds - Condello, G.; Reynolds, E.; Foster, C.; de Koning, J. J.; Casolino, E.; Knutson, M.; Porcari, J. P. (Journal of Sports Science & Medicine, 2014)
This study aimed to investigate whether ventilatory (VT) and respiratory compensation (RCT) thresholds could be derived from percentages of maximal running speed (Vmax). During the model building phase (1), VT & RCT of 31 competitive level athletes were identified with respiratory gas exchange. During the cross-validation phase (2), 20 subjects performed a treadmill test to identify Vmax and then they performed 30-min runs at velocities 2SE below or above the velocity at VT and RCT derived from (1), with measurement of blood lactate [BL], RPE, heart rate (HR), and speech comfort. Phase (1) revealed that VT and RCT were reached at 67 ± 9% and 84 ± 6% of Vmax. In (2) sustained running 2SE below VT (64% Vmax) was associated with the ability to finish 30-min, with low and constant [BL] (~2.5 mmol.l-1), moderate RPE (~3.0-3.5), a small HR drift, and ability to speak comfortably. Conversely, running at 2SE above RCT (86% Vmax) was associated with the inability to finish 30-min (18.5 ± 2.5 min to fatigue), increasing [BL] (end-exercise = 11.9 ± 0.9 mmol.l-1), high RPE (end-exercise = 8.9 ± 1.0), large HR drift (end-exercise = 98 ± 3% HRmax), and inability to speak comfortably. Simple percentages of Vmax (=64% and =86%) obtained from a treadmill test without gas exchange, may be useful for prescribing exercise training intensities.